PENGARUH DIGITAL EKONOMY PADA POLA BELANJA GENERASI MILENIAL DI ERA DIGITAL ECONOMY - Risca Olivianti; Maria Yovita R.Pandin (Juremi: Jurnal Riset Ekonomi, 2024)
This study uses a targeted quantitative causality method to observe the impact of the digital economy on the shopping patterns of the millennial generation in the digital economic era. Do shopping patterns have an influence on the millennial generation in the digital economic era. This type of research is quantitative causality using purposive techniques with the criteria of the millennial generation aged 24-39 who are residents of Ujungpangkah Gresik sub-district. This research involved distributing a questionnaire in the form of a Google form distributed via WhatsApp. The results of this study show that the digital economy has a positive influence on shopping patterns in the millennial generation